Students’ Accuracy in Using Auxilary Verbs in Asking Question during Teaching and Learning in Classroom - Yoga Ferdiansyah; Yupika - Maryansyah (Teaching English and Language Learning English Journal, 2022)
The objective of this research was to investigate the students’ accuracy of using auxiliary verbs in asking questions during teaching and learning in classroom at the Second Semester English Study Program of UMB. This research used descriptive method since the researcher wants to know and describe the accuracy of using auxiliary verb in asking questions in teaching and learning activity in the classroom at second semester of University of Muhammadiyah Bengkulu. The object of this research was questions which asked by the students while teaching learning process at second semester English Study Program of University of Muhammadiyah Bengkulu. The data was obtained in four meetings. The instrument of this research was an observation checklist. The researcher recorded the activity in the classroom then observe the students’ questions which contained auxiliary verb. The finding of this research showed that the students’ accuracy of using auxiliary verbs in asking questions during teaching and learning in classroom at the Second Semester English Study Program of UMB were good with percentage 81%. Keywords : Students’ Accuracy, Auxiliary Verbs in Asking Question